Minimizing greenhouse gas emissions from leachate treatment by using zeolite column - Hakki Gülşen; Pelin Yapıcıoğlu (Carbon Management, 2021)
In this study, by using a fluidized bed reactor, anaerobic treatment of young landfill leachate was performed to observe carbon dioxide (CO2), methane (CH4) and nitrous oxide (N2O) emissions. Greenhouse gas (GHG) emissions from an anaerobic fluidized bed reactor (AFBR) were calculated through a developed model based on IPCC approach. During 270 days of operation, it was reported that CH4 was the major emitted greenhouse gas with the highest values. Also, N2O and CO2 have been emitted from an AFBR. To minimize the GHG emissions, a zeolite column reactor was used for the reduction of the GHG emissions during 60 days of operation. Static chamber method was applied to measure the emissions from the zeolite column reactor. It was observed that GHG emissions from leachate treatment was minimized by applying an adsorption process with zeolite. CO2 emission was 0 at the end of 46 days. N2O emission was zero at 27th day. The emission of methane was also reduced up to 32%. The emission of CH4 emission was minimized at nearly 4.75 kg CO2e/d. Thus, it can be said that zeolite could adsorb CO2, CH4 and N2O gases and minimize GHG emissions.